2023
DOI: 10.1186/s12935-023-02925-7
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as the critical regulators of autophagy-mediated cisplatin response in tumor cells

Abstract: Chemotherapy is one of the most common therapeutic methods in advanced and metastatic tumors. Cisplatin (CDDP) is considered as one of the main first-line chemotherapy drugs in solid tumors. However, there is a high rate of CDDP resistance in cancer patients. Multi-drug resistance (MDR) as one of the main therapeutic challenges in cancer patients is associated with various cellular processes such as drug efflux, DNA repair, and autophagy. Autophagy is a cellular mechanism that protects the tumor cells toward t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 209 publications
0
5
0
Order By: Relevance
“…[18][19][20] Some micro-RNAs (miRNAs) are closely correlated with MDR induction because they regulate MDR relevant gene expression. [21][22][23] In the current study, we confirmed HCSP4 targeting specificity to CK2α and designed a novel liposomal DOX delivery formulation using HCSP4 as a targeting fragment and a newly identified miRNA (miR125a-5p) as the inhibitor of CK2α and MDR induction, then the new drug was tested for its HCC therapeutic efficacy and mechanism in vitro.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…[18][19][20] Some micro-RNAs (miRNAs) are closely correlated with MDR induction because they regulate MDR relevant gene expression. [21][22][23] In the current study, we confirmed HCSP4 targeting specificity to CK2α and designed a novel liposomal DOX delivery formulation using HCSP4 as a targeting fragment and a newly identified miRNA (miR125a-5p) as the inhibitor of CK2α and MDR induction, then the new drug was tested for its HCC therapeutic efficacy and mechanism in vitro.…”
Section: Introductionmentioning
confidence: 61%
“…[ 18–20 ] Some micro‐RNAs (miRNAs) are closely correlated with MDR induction because they regulate MDR relevant gene expression. [ 21–23 ]…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating studies have demonstrated miRNAs directly target PI3K or its downstream components, which critically contributes to extensive cell events, including autophagy. , A previous study revealed that miR-155 mediated autophagy via directly targeting PI3K-AKT-mTOR in Schwann cells . We hypothesized that PI3K was also targeted by miR-155 to regulate Pec 1-induced autophagy inhibition in MH-S cells.…”
Section: Resultsmentioning
confidence: 92%
“…Autophagy is a conserved cellular process that is responsible for degradation of intracellular proteins and organelles [ 145 , 146 ]. It can be activated in both normal and stress condition to provide required metabolic substrates for the cell survival.…”
Section: Wnt/β-catenin and Pi3k/akt Signaling Pathwaysmentioning
confidence: 99%